Le Web des internautes - Sébastien Rouquette (Communication)
As shown in a comparative rereading of the statistical literature on the uses of the Web, two types of surfing occupy the majority of users: the practical Web and the entertaining Web.From this, two types of conclusions can be drawn.The first is that because of a “media” or “economic” bias, most of the “hit parades” often give the illusion of an “internet revolution” and of the average user. The second is that the users judged to be “trivial” play both the role of revealing the technical evolutions of the internet as well as of the changing social, familial, or professional constraints which most internet users face.